Preliminary - García Aristizábal, Edwin Fabián (Revista Facultad de Ingeniería Universidad de Antioquia, 2014)
Revista Facultad de Ingeniería is a journal that started its official publication in 1984. Since then, it is aimed to contribute to the diffusion of knowledge within the national and international academic community throughout the publication of high-quality research results. The Journal focuses on original works which mainly include experimental studies, numerical analyses, case studies, and bibbliographic reviews that provide a significant contribution to engineering and technology areas in all disciplines (Electronic, Electrical, Computer Science, Mechanic, Chemical, Environmental, Materials, Sanitary, Civil, Telecommunications, Industrial Engineering, and Bioengineering).